Raymond Brown, 'The Jews,' and the Gospel of John from apologia to apology - Cronin, Sonya (London New Delhi New York Bloomsbury, 2015)
"Until the mid-1960s, while most commentators of the Gospel of John were aware of a polemic against 'the Jews,' they did not consider it with reference to contemporary ethical discussion. A shift in focus in Johannine scholarship is noticeable from the mid-1960s and 1970s to the present, where commentators began to connect the Gospel's polemic against 'the Jews' with potential anti-Judaism in the text. As yet, very little work has been done to answer the question of how this change in sensitivity came about. This book is a historiography of one scholar's growing awareness of potential anti-Judaism in the Gospel of John with the intention of using this individual history to explain the larger trend in biblical studies. Sonya Cronin examines the published work of Raymond Brown, a prominent Catholic New Testament scholar, between the years 1960-1998. The book contextualizes Brown's work by evaluating the impact of ecclesiastical statements and the influence of earlier and contemporary Johannine scholarship on Brown's biblical interpretation, and then posits theories as to why change occurs at specific times."--Bloomsbury Publishing
Includes bibliographical references and index
Also issued in print.
Electronic reproduction; Available via World Wide Web
Reproduktion
Barrierefreier Inhalt: Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Keywords: Apologetics; Judaism; Bible -- Criticism, interpretation, etc